Effect of sodium ascorbate on the bond strength of silorane and methacrylate composites after vital bleaching - Eda Guler; Nihan Gonulol; Ozgun Yusuf Ozyilmaz; Ali Cagin Yucel (Sociedade Brasileira de Pesquisa Odontológica, 2013)
We investigated the effect of sodium ascorbate (SA) on the microtensile bond strengths (MTBSs) of different composites to bovine enamel after vital bleaching with hydrogen peroxide (HP) or carbamide peroxide (CP). Thirty bovine incisors were randomly divided into five groups and treated with no bleaching application (control), 35% HP alone, 35% HP + 10% SA for 10 minutes (HP + SA), 16% CP alone, or 16% CP + 10% SA for 10 minutes (CP + SA). Specimens were restored with Silorane adhesive and Filtek Silorane composite (designated as S / group) or with Clearfil SE bond and Filtek Supreme XT (designated as F / group). Composite build-up was created on the enamel. Sectioned specimens (n = 10 per group; 1 mm2; cross-sectional area) were created and stressed in a universal testing machine at 1 mm/min crosshead speed. The application of 10% SA immediately after bleaching with 16% CP or 35% HP increased the enamel MTBS, regardless of the adhesive / composite resin used. The resulting MTBS values were similar to those of the control groups. Use of 16% CP and 35% HP alone decreased the enamel MTBS, regardless of the adhesive / composite resin used, with F / CP + SA = F / HP + SA = F / CP = S / CP + SA = S / HP + SA = S / C > S / CP = S / HP = F / CP = F / HP (p < 0.05). We concluded that the application of SA for 10 minutes immediately after vital bleaching increases the enamel BS for dimethacrylate- and silorane-based composites